FENOMENA TENTARA BAYARAN DAN KEMUNGKINAN IMPLEMENTASINYA DI INDONESIA - Marnani, Christine Sri (Universitas Jenderal Ahmad Yani, 2023)
The phenomenon of using mercenaries in armed conflicts has been a controversial issue around the around the world since BC. However, until now the phenomenon still exists, especially since Russia's attack on Ukraine in 2022. This global phenomenon raises a question,